The Safety and Efficacy of Microwave Endometrial Ablation After Endometrial Curettage Without Hormonal Pretreatment - Ming-Chao Huang; Chih-Ping Chen; Tsung-Hsien Su; Kung-Liahng Wang; Yuh-Cheng Yang; Yuh-Ming Hwu (Elsevier, 2007)
Objective: To evaluate the safety and efficacy of a microwave endometrial ablation (MEA) procedure to treat patients with menorrhagia after endometrial curettage but without medical pretreatment. Materials and Methods: From February to September 2001, 19 eligible and consenting premenopausal women with menorrhagia underwent endometrial curettage, immediately followed by MEA. No medical pretreatment with gonadotropin-releasing hormone (GnRH) analogues or danazol was given for endometrial preparation. The severity of menorrhagia was assessed using the menstrual score. The patients were followed up for at least 3 years. Results: Of the 19 women, 17 had completed at least 3 years' follow-up. Fourteen patients (82%) were satisfied with the posttreatment menstrual status, comparable with those patients receiving medical pretreatment of other studies (78-94%). The mean menstrual score was 11.8 before treatment and 1.95, 2.25, 2.2, 2.1 and 2.1 at 3, 6, 12, 24 and 36 months posttreatment, respectively. Of the 12 patients who complained of dysmenorrhea before surgery, six (50%) showed improvement. Three patients had hysterectomy; they all had adenomyosis and dysmenorrhea which did not respond to medical analgesics. Conclusion: MEA preceded by endometrial curettage instead of hormonal pretreatment had results comparable to those of other studies in which the patients received hormones for 4-6 weeks before MEA. Endometrial curettage is an alternative to drug pretreatment.